Crustal structure and geodynamics of the eastern Qilian orogenic belt, NE margin of the Qinghai-Tibet plateau, revealed by teleseismic receiver function - Cheng, Yongzhi; Gao, Rui; Chen, Jiuhui; Lu, Zhanwu; Li, Wenhui; Wang, Guangwen; Chen, Hao; Han, Rubing; Niu, Xiao; Wu, Guowei; Chen, Si; Cai, Yuguo (Frontiers in Earth Science, 2023)
The eastern segment of the Qilian orogenic belt, comprising the Linxia block and Longzhong block, is at the Qinghai–Tibet Plateau’s northeastern margin. The area has experienced multiple tectonic events, including closure of the Qilian Ocean, convergence of the North China block and Qilian terrane, and collision of the Indian and Eurasian plates, forming a complex tectonic framework. To investigate the area’s geological evolution and the suture’s current location between the blocks, we used 3-year data recorded by 33 portable ChinArray II broadband stations (2013–2016). Using three teleseismic P-wave receiver function methods, H-κ stacking and common conversion point stacking (CCP), crustal structure, Poisson’s ratio, and Moho morphology were obtained at 33 stations. The results are described as follows: 1) The Maxianshan fault is an important boundary fault that divides the Linxia block and Longzhong block. The Linxia block’s layered crustal structure is obvious, and there is a low-velocity anomaly in the middle and lower crust, which may contain saline fluid and has Japanese-type island arc characteristics. 2) The layered structure of the Longzhong block’s upper crust is significant, while the middle and lower crust’s layered structure is weak with weak low-velocity characteristics and oceanic-island basaltic crust characteristics. The Longzhong block may have originally been formed by Mariana-type island arcs. 3) The Conrad interface and Moho lateral variation in the Ordos block’s southwestern margin are weak, showing stable craton characteristics. 4) Our results show that the Maxianshan fault cuts through the Earth’s crust and is a continuous west-dipping negative seismic phase in the Common Conversion Point section. The fault zone is the suture line between the Linxia block and Longzhong block. 5) The middle and upper crust of the Liupanshan tectonic belt is thrust upwards on the Ordos block’s southwestern margin, providing deep structural evidence of the Cenozoic uplift of the Liupanshan structural belt.